2020
DOI: 10.3389/fpls.2020.00460
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Long-Distance Signaling and Communication Between Rootstock and Scion in Grafted Vegetables

Abstract: Grafting is widely used in fruit, vegetable, and flower propagation to improve biotic and abiotic stress resistance, yield, and quality. At present, the systemic changes caused by grafting, as well as the mechanisms and effects of long-distance signal transport between rootstock and scion have mainly been investigated in model plants (Arabidopsis thaliana and Nicotiana benthamiana). However, these aspects of grafting vary when different plant materials are grafted, so the study of model plants provides only a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 122 publications
0
35
0
Order By: Relevance
“…The interaction between scion and rootstock is bi-directional. Various constituents, including ions, nutrients, hormones, peptides/proteins, small organic molecules, and nucleic acids, have been shown to move across the graft union through the phloem and xylem ( Albacete et al, 2015 ; Lu et al, 2020 ). As a result, grafting triggers new systemic signals that are able to interact with genes involved in metabolic processes, hormone signaling, the activity of transcription factors, physiological responses to environmental stimuli, and others ( Albacete et al, 2015 ; Warschefsky et al, 2016 ; Lu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between scion and rootstock is bi-directional. Various constituents, including ions, nutrients, hormones, peptides/proteins, small organic molecules, and nucleic acids, have been shown to move across the graft union through the phloem and xylem ( Albacete et al, 2015 ; Lu et al, 2020 ). As a result, grafting triggers new systemic signals that are able to interact with genes involved in metabolic processes, hormone signaling, the activity of transcription factors, physiological responses to environmental stimuli, and others ( Albacete et al, 2015 ; Warschefsky et al, 2016 ; Lu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This rootstock-to-scion transitivity was found to be associated with mobile siRNA, which is formed in cells through cleavage of dsRNA ( Liu and Chen, 2018 ; Choudhary et al, 2019 ; Zhang et al, 2019 ). Numerous studies revealed extensive exchange of endogenous and exogenous small RNA (sRNA), including siRNA and micro RNA (miRNA), in woody and herbaceous plant species between intra- and intergeneric grafts ( Pyott and Molnar, 2015 ; Kyriacou et al, 2017 ; Kehr and Kragler, 2018 ; Liu and Chen, 2018 ; Choudhary et al, 2019 ; Zhang et al, 2019 ; Lu et al, 2020 ). This gives rise to an opportunity to design transgrafted plum trees eliciting an abundant amount of dsRNA/siRNA mobile signals in the transgenic rootstock to achieve PPV resistance in a scion.…”
Section: Introductionmentioning
confidence: 99%
“…When looking at move-up mRNAs, differing from Csa mRNAs, 531 Cmo mRNAs were enriched in carbon fixation in photosynthetic organ of energy metabolism, and peroxisome of cellular process ( Tables S5 and S6 ). Some metabolites, mRNAs, and proteins were reported to produce in the rootstock spread/transport/migrate via cell-to-cell to the ground of the grafted vegetables [ 39 , 40 ]. Pumpkin rootstocks are widely used in cucumber grafting cultivation due to their strong vigor, including enhancing photosynthesis, keeping stability of plasma membrane, and so on [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rootstock effects can go further and influence properties typically attributed to the clonal scion such as fruit sensorial and nutritional quality—e.g., texture, sugar content, acidity, pH, flavor, and color ( Giorgi et al, 2005 ; Gullo et al, 2014 ; Balducci et al, 2019 ), cold tolerance and shoot pest and pathogen resistance ( Rubio et al, 2005 ; Goldschmidt, 2014 ). These combined effects are influenced by phylogenetic distance and stem anatomy ( Wulf et al, 2020 ) and are mechanistically due to large-scale movement of water, proteins, and nutrients ( Little et al, 2016 ) or long-distance signaling ( Lu et al, 2020 ) via hormones, messenger RNAs, and small RNAs ( Wang et al, 2017 ; Loupit and Cookson, 2020 ; Rasool et al, 2020 ). Despite shared physiological processes account for the overall trait variation, the interconnection of all contributing variables (i.e., rootstock genotype, scion genotype, and environment) obscures individual contributions to phenotypic variation ( Albacete et al, 2015 ; Warschefsky et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%